Legal analysis of consumer data protection in metaverse transactions: a case study of NFT and digital assets - Virly Vidiasti Sabijanto (Cessie : Jurnal Ilmiah Hukum, 2026)
This study analyzes consumer data protection in metaverse transactions, specifically related to NFTs and digital assets, within the Indonesian legal framework. The study's findings indicate that despite existing legal frameworks such as the Consumer Protection Law and the Personal Data Protection Law, existing regulations are not yet comprehensive in addressing the unique risks inherent in virtual environments. This study aims to identify legal challenges and analyze the adequacy of national regulations in protecting consumers' personal data and digital assets in the metaverse. Normative legal research methods were used to examine existing laws and regulations, such as Law No. 8 of 1999 concerning Consumer Protection and Law No. 27 of 2022 concerning Personal Data Protection. There are significant regulatory gaps between the existing legal framework and the dynamics of metaverse transactions, particularly regarding cross-border jurisdictions, the legal status of digital assets, and cybersecurity threats. Legislative reform and the participation of all stakeholders are needed to strengthen the consumer and personal data protection framework in the era of evolving metaverse technology.